An Empirical Analysis of Green Experiential Loyalty: A Case Study. Issue 1 (2nd January 2019) - Wu, Hung-Che; Cheng, Ching-Chan
Abstract: The purpose of this study is to elaborate the structural relationships among the experiential quality dimensions, experiential trust, emotional attachment, experiential image, switching experience, experiential satisfaction, and experiential loyalty from the green perspective. The study findings are based on structural equation modeling (SEM) analysis of a convenience sample of 560 customers at one green restaurant in Taipei City, Taiwan. The findings show that investing resources in an increase in the experiential quality dimensions and a decrease in green switching experience is useful to enhance green experiential trust, green emotional attachment, green experiential image, green experiential satisfaction, and green experiential loyalty.